Pengaruh Kecepatan Sliding Vertical Terhadap Hasil Pengelasan Material Karbon Rendah Menggunakan Proses Pengelasan Smaw Sistem Sliding Adaptive Vertical - Andreas Prasetyo; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Electric arc welding wrapped electrodes or known as SMAW (Shielded Metal Arc Welding) is one of the welding technologies which have several advantages such as large currents that can be varied as a heat source, and easy to use in various welding positions. In order to get good welding, the angle and speed of welding must be concerned. This study uses a sliding adaptive vertical system that varies the welding speed and angle. Observation was done by observing visually and mechanical properties were tested by a tensile test. The material used low steel (mild steel), the seam used V steam with angle 60 ° and the electrode used the E6013 KOBE RB-26 electrode with 3.2 mm diameter. This study used 9 specimens with the lowest tensile strength of 468.11 Mpa and the highest value is 496.53 Mpa. Micro structure is influenced by several factors such as heat input, cooling rate, weld speed, and current strength. In this study the weld metal area has a large grain structure than base metal and HAZ (Heat Affected Zone).Keywords: smaw welding, sliding adaptive vertical, electrode angle, HAZ.